2018
DOI: 10.1186/s12889-018-5066-9
|View full text |Cite
|
Sign up to set email alerts
|

The identification of risk factors associated with patient and healthcare system delays in the treatment of tuberculosis in Tabriz, Iran

Abstract: BackgroundTuberculosis (TB) is a serious health concern, particularly in developing countries. Various delays, such as patient delay (PD) and healthcare system delay (HSD) in the TB process, are exacerbating the disease burden and increasing the rates of transmission and mortality in various global communities. Therefore, the aim of this study is to identify risk factors associated with PD and HSD in TB patients in Tabriz, Iran.MethodsA cross-sectional study was conducted on 173 TB patients in Tabriz, Iran fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
9
3
Order By: Relevance
“…Consistent with other studies we also found an association of lower education level with longer delay [10] , indicating a need for interventions to increase awareness and knowledge about TB in the general population. Our findings of longer delay among men is supported by some [ 31 , 32 ], but not all studies [ 11 , 12 ]. The association between health insurance ownership and earlier presentation and treatment is consistent with the findings of a recent study in Vietnam; having health insurance influences patients’ behavior towards seeking care from a formal HCP [33] .…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with other studies we also found an association of lower education level with longer delay [10] , indicating a need for interventions to increase awareness and knowledge about TB in the general population. Our findings of longer delay among men is supported by some [ 31 , 32 ], but not all studies [ 11 , 12 ]. The association between health insurance ownership and earlier presentation and treatment is consistent with the findings of a recent study in Vietnam; having health insurance influences patients’ behavior towards seeking care from a formal HCP [33] .…”
Section: Discussionsupporting
confidence: 87%
“…The majority of front-line healthcare workers, as represented by DACs and DTLCs surveyed, demonstrated opportunity for knowledge improvement on the use of molecular diagnostics, and knowledge was more deficient for GenotypeMTBDR plus compared to XpertMTB/RIF, and for both technologies in DACs compared to DTLCs. While these knowledge gaps are not dissimilar from recent studies of front-line healthcare workers in other sub-Saharan African countries and elsewhere regarding molecular diagnostics for TB [17], the scale of effect was profound. Only 40% of previously treated TB cases were tested for MDR-TB, lower than the global estimate of 60% [1], and when accounting for the those tested but for whom results were not communicated to the clinic, only 30% of all cases of presumed MDR-TB received the opportunity for the most accurate and effective treatment, which is exceptionally low compared to other settings [18].…”
Section: Discussioncontrasting
confidence: 56%
“…Factors contributing to patient delay (PD) include family size, occupation, the income of the family, stigma, knowledge about TB, first visit informal provider, distance to the health facility, and self-medication [11][12][13][14]. There are growing numbers of studies on diagnostic and treatment delays.…”
Section: Introductionmentioning
confidence: 99%